Number of human-brown bear ( Ursus arctos ) and human-Persian leopard ( Panthera pardus ) incidents by type of primary human activity (a) and attack motivation (b), Iran, 2012–2020. - Jamshid Parchizadeh (11172294); Jerrold L. Belant (7852490) (2021)
Number of human-brown bear ( Ursus arctos ) and human-Persian leopard ( Panthera pardus ) incidents by type of primary human activity (a) and attack motivation (b), Iran, 2012–2020.